(untitled) (Journal of actual problems of jurisprudence, 2018)
In this article objects administrative procedural legal relationship which are disbanded by modern scientists of an administrative procedural law are considered. Key words: administrative procedural legal relationship, Law, an object pravootnoienie process administrativniy.